Optical and Photocatalytic Properties of BiVO4 Particles Derived via rapid Synthesis Sonochemical Process - Thanaphon Kansaard (Thai Journal of Nanoscience and Nanotechnology, 2023)
Currently, the environmental pollutions are very critical to human health and nature. For solving these problems, photocatalytic degradation by metal oxide materials is among effective organic compound decomposition methods. BiVO4 is an attractive material due to light activation under visible irradiation. This work focuses on the rapid synthesis of BiVO4 via sonochemical process within 30 min. Ultrasonic irradiation time determined as a crucial parameter of particle formation was designated in range of 0 - 30 min. Crystallinity of synthesized materials was characterized by X-ray diffraction technique. Optical band gap energy was calculated by Kubellka-Munk function of collected data from diffuse reflectance spectroscopy and photoluminescence technique was used to determine the photogenerated behavior of photocatalyst material. Raman spectroscopy and X-ray absorption spectroscopy were employed to investigate their chemical bonding and oxidation state, respectively. Among all samples, the sample synthesized at 30 min irradiation time exhibited pure monoclinic structure with optical band gap of 2.5 eV and superiority in photodecomposition of RhB under visible light exposure.
Keywords: Gas Sensing Nanomaterials and Sensors; Advanced Photocatalysis Techniques